Peranan Media Pembelajaran Dalam Pendidikan Islam - Chairunnisa Chairunnisa; Najwa Ammara Jauza; Dita Adinda Fitri; Hafiz Khudri Tanjung; Syahril Amin (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
In its development, science and technology continue to push for changes in the utilization of technological results in the learning process. Learning media is one of the ways and efforts in the learning process carried out by the teacher, namely using learning media. By using learning media the teacher will more easily teach the subject matter and students will more easily understand the lesson. The role of learning media in the learning and teaching process is very important for educators to carry out at this time, because the role of learning media can be used to channel messages from senders to recipients and through learning media can also help students to explain something conveyed by educators. Therefor the research is aimed at analyzing how the role and function of instructional media specifically in Islamic education. This research uses qualitative methods with literature studies. The subject of this research was carried out in an analytical manner by collecting sources such as books, or the results of previous related studies, then analyzing them. The implication of this research is to be able to find out the role of learning media in Islamic education so that the goals of education in Islam can be achieved.